Bazyliszek - Kwietniewska, Marzena; Stefaniak, Anna.; Stefaniak, Lech. (Krakow : KANWA, 1993)
A fairy tale about a magical iguana. Ages 3-6.
Title from cover.
On board pages.
Keywords: Iguanas -- Juvenile literature